Mathematical connections: An analysis of students' ability in solving mathematical problems based on learning styles - Bete, Hendrika; Salsinha, Cecilia Novianti; Naimnule, Maria (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
The purpose of this study was to analyze students' mathematical connection abilities in solving mathematical problems based on learning styles using descriptive qualitative research. The subjects of the study were students of SMAN Binino by taking 3 students, namely 1 dominant visual student, 1 dominant auditory student and 1 dominant kinesthetic student. Data were obtained from questionnaires, written tests and interviews. The analysis was carried out by collecting data, reducing data, and drawing conclusions. The results of the study showed that the mathematical connection abilities of students with a visual learning style were that students were able to make connections between topics, mathematical connections with other fields of science and mathematical connections of students with everyday life . The mathematical connection abilities of students with an auditory learning style were that students were able to make connections between topics, mathematical connections of students with everyday life but were unable to make mathematical connections with other fields of science. The mathematical connection abilities of students with a kinesthetic learning style were that students had difficulty in understanding concepts and doing calculations so that students were unable to make mathematical connections in solving problems.